Man-cessions, Fiscal Policy, and the Gender Composition of Employment - Falko Jüßen; Christian Bredemeier; Roland Winkler (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
In recessions, predominantly men lose their jobs, which has been described by the term "mancessions". Against this background, we analyze whether fiscal expansions foster job creation predominantly for men. Yet, we find empirically that fiscal shocks lead to employment growth that is larger for women than for men. We show that the gender-specific employment effects of fiscal policy are driven by disproportionate employment changes in female-dominated occupations, specifically so-called "pink-collar" occupations. We develop a business-cycle model that explains these occupational employment dynamics as a consequence of differences in the substitutability between capital and labor across occupations.
Keywords: J21; E62; J16; 330